Factors influencing delayed clearance of high dose methotrexate (HDMTX) in pediatric, adolescent, and young adult oncology patients - Mosleh, Ema; Snyder, Stacy; Wu, Ningying; Willis, Daniel N.; Malone, Rema; Hayashi, Robert J. (Frontiers in Oncology, 2023)
Purpose: To identify modifiable risk factors associated with prolonged clearance of methotrexate in pediatric, adolescent, and young adult (AYA) oncology patients receiving high dose methotrexate (HDMTX).: A single institution, retrospective chart review of patients receiving HDMTX between 2010-2017. Patients had a diagnosis of either leukemia or osteosarcoma. Data included demographics, concurrent intravenous (IV) medications, IV fluids (IVF) administered, urine output (UO), and rises in serum creatinine (RSC) reflective of renal toxicity (RT). Outcome measures included 1) delayed targeted MTX clearance (DC), 2) actual time to clearance (TTC) and 3) length of stay (LOS).Results: Data from 447 HDMTX administrations were analyzed. The sample consisted of 241 (54%) osteosarcoma encounters, and 206 (46%) leukemia encounters, with an average patient age of 12.7 years. Multivariate analysis showed that DC was associated with the diagnosis of leukemia (OR 7.64, p <.0001), and less UO on day 1 (OR 0.76, p=0.005). Increased TTC was associated with increasing age (RR 1.02, p<0.0001), higher 24-hour MTX levels (RR 1.001, p=0.012) and 48-hour MTX levels (RR 1.02, p<0.0001), RT (RR 1.004, p<0.0001), use of IV lorazepam (RR 1.08, p=0.001) and IV metoclopramide (RR 1.08, p<0.001) both on day 3. Like TTC, LOS was affected by MTX levels at 24 (RR 1.001, p=0.025) and 48 hours (RR 1.03, p<0.0001), RT (RR 1.006, p<0.0001), total IV medications on day 3 (RR 1.042, p<0.0001), and the use of leucovorin on day 2 (RR 0.93, p=0.002).Multiple modifiable risk factors were identified which can be leveraged to improve HDMTX clearance. Subsequent efforts will assess whether acting on such risk factors can improve MTX clearance and shorten LOS.* The multivariate models were fitted on risk factors selected via stepwise process using a significant level of 0.05 as both the entry and stay criteria. The table exclusively presents statistically significant findings; full tables can be found in supplementary material.